In vitro comparison of acyclovir, ganciclovir and cidofovir against equid alphaherpesvirus 3 and evaluation of their efficacy against six field isolates = Comparación in vitro de aciclovir, ganciclovir y cidofovir contra alfa-herpesvirus equino 3 y evaluación de la eficacia de los mismos frente a 6 aislamientos de campo del virus - Vissani, Maria Aldana (2018)
Equid alphaherpesvirus 3 (EHV3) is the etiological agent of equine coital exanthema (ECE), which is a venereal, highly contagious disease, characterized by the formation of papules, vesicles, pustules and ulcers on the external genitalia of mares and stallions. EHV3 remains in a latent state after a successful infection and there are latently infected animals in which the virus is reactivated and generally re-excreted subclinically. There are no available vaccines for this condition and prevention is based on the clinical examination of mares prior to mating, which allows to segregate those showing clinical signs. As this approach does not eliminate the risk of contagion in stallions from subclinically infected mares, there is a need for a specific EHV3 treatment. Nowadays, there exist various antiviral compounds of proven effectiveness for other alphaherpesviruses affecting humans and animals. The aim of the present study was to compare the efficacy of three antiviral compounds, acyclovir, ganciclovir and cidofovir against EHV3 in vitro, and to assess their efficacy against six EHV3 Argentinian field isolates. To determine the efficacy of these compounds in vitro, three parameters were analyzed: reduction of plaque number, reduction of plaque size and reduction of viral production. Additionally, the effectiveness of the three compounds at an optimum concentration previously determined in this study was investigated for the EHV3 field isolates. Based on our results, ganciclovir was the most potent antiviral compound to reduce EHV3 replication in vitro and may thus be a valuable candidate for treatment and prevention of ECE in mares and stallions.